Benign prostatic hyperplasia. (January 2013) - Parnham, Arie; Haq, Ahsanul
Male Lower Urinary Tract symptoms (LUTs) and Benign Prostatic Hyperplasia (BPH) provide a significant proportion of the core urologists workload, and will continue to do so for the foreseeable future with an increasingly elderly population. This review sets out to provide an overview of the current understanding around BPH and male LUTs as well as investigations and treatment options.